Reducing the impact of peer victimization on adolescent insomnia: Which is more important, peers or family support? - Hu, Siyi; Wang, Yuxuan; Wan, Qirong; Chen, Zhenhua; Fan, Jingyi (Frontiers in Psychiatry, 2025)
BackgroundAdolescent insomnia is a global public health issue, with peer victimization identified as one of the risk factors. However, some adolescents are able to resist the negative impact of peer victimization, and the protective mechanisms underlying this resilience require further clarification. This study aims to evaluate the moderating roles of friendship quality and family functioning on the effects of peer victimization on insomnia.MethodsParticipants (n=506, age=14.49 ± 0.68, 54.5%female) from Hubei, China, completed the Insomnia Severity Index (ISI), Multidimensional Peer Victimization Scale (MPVS), Friendship Quality Questionnaire (FQQ), and Family Adaptation, Partnership, Growth, Affection, and Resolve (APGAR).ResultsThe more severe the peer victimization, the higher the level of insomnia among adolescents. Family functioning moderated the relationship between peer victimization and insomnia severity, but no moderating effect of friendship quality was found.ConclusionThe results suggest that high family functioning can mitigate the impact of peer victimization on insomnia. In the screening and intervention for peer victimization and insomnia among adolescents, the importance of family functioning should be emphasized, while recognizing that friendship quality may not play a significant role.